Awareness on conservation of mangrove among the community of Kuala Sepetang Taiping, Perak / Nur Idzhainee Hashim, Azman A Rahman and Nor Hanisah Mohd Hashim - Hashim, Nur Idzhainee; A Rahman, Azman; Mohd Hashim, Nor Hanisah (2017)
The State of Perak is fortunate to be endowed with such a unique coastal heritage, "The Matang Mangrove". The area covers approximately 40,466 hectares of Mangrove Swamp Forest in the Larut, Matang and Kerian District and managed by the Perak Forestry Department since 1904. It has been acclaimed to be one of the best-managed mangrove forests in the world. Mangrove forest is one of the most productive and biodiversity wetlands on earth. These unique coastal tropical forests are among the most threatened habitats in the world and they are naturally grown and have less economic value, therefore, people and the community ignored the crucial role played by the forest. Study on the exploitation of mangrove ecosystem conservation at Kuala Sepetang, Taiping Perak found that few people from the area lack of knowledge and information of the crucial role played by the forest. They are not guilty of disturbing the mangrove forest with so many activities such as exploitation for aquaculture, industrial projects, cultivation, fire wood, charcoal, piling log, and so on without realizing that these activities if continued without efficient management and action, sooner or later will disappearing the mangrove ecosystems. Disappointingly, some respondents disagreed to contribute some amount of money to support the government effort to preserve the mangrove forest thus, the authority and the government need to increase the awareness among the communities and as a whole by doing promotion and educate the people regarding the crucial of the mangrove forest to the nature must be put in syllabus as a national agenda. So that citizens will appreciate of preserving its continual functions for forestry purposes regardless the gender, ethnics, age and level of education. Therefore, the study aims are to evaluate the awareness on conservation of these precious intertidal forests among the community for the benefits of all.